Ent-Abietane diterpenoids with anti-neuroinflammatory activity from the rare Chloranthaceae plant Chloranthus oldhamii. Issue 20 (28th April 2016) - Xiong, Juan; Hong, Zhi-Lai; Xu, Peng; Zou, Yike; Yu, Shang-Bo; Yang, Guo-Xun; Hu, Jin-Feng
Abstract : Twelve new ent -abietane diterpenoids including four unprecedented structures were isolated and characterized from the rare plant Chloranthus oldhamii . Abstract : Twelve new ent -abietane diterpenoids, chlorabietins A–L (1–12 ), were isolated from the roots of Chloranthus oldhamii . Their structures and absolute configurations were determined by extensive spectroscopic analyses, X-ray diffraction, and experimental/calculated electronic circular dichroism (ECD) spectroscopy. Among the new isolates, chlorabietins D (4 ) and E (5 ) are the first two naturally occurring 8-spiro-fused 9, 10- seco-ent -abietanes containing an unexpected cis -fused A/B ring system. Chlorabietin F (6 ) is a rare chinane-type diterpenoid featuring a hitherto unknown C-ring cleavage between C-13 and C-14, which might be derived from a common precursor of the above spiro-diterpenoid epimers4 and5, and their biosynthetic relationships are briefly discussed. Meanwhile, chlorabietin I (9 ) is the first representative of the abietane-type diterpenoids possessing a tetrahydrofurano function bridging C-6 and C-19. Chlorabietins B (2 ), C (3 ), F (6 ), and G (7 ) showed anti-neuroinflammatory effects by inhibiting the nitric oxide (NO) production in lipopolysaccharide (LPS)-activated murine BV-2 microglial cells, with IC50 values ranging from 16.4 to 33.8 μM.